THE INFLUENCE OF USING THE MIRO APPLICATION ON THE UNDERSTANDING LEVEL OF PLANE GEOMETRY IN ELEMENTARY EDUCATION - Andi Asrafiani Arafah; Sukriadi Sukriadi; Ririt Riyanti (JURNAL NALAR PENDIDIKAN, 2024)
The aim of this research is to find out how the use of the Miro application affects the level of understanding of plane geometry in basic education. The type and research approach used in this research is quantitative pre-experimental designs with one group pretest posttest designs method. The Shapiro-Wilk normality assumption test shows a normally distributed value, namely 0.372 and hypothesis testing using the Paired Sample T-test shows significant results, namely k